A Facile and Environmental‐Friendly Approach to Synthesize S‐Doped Fe/Ni Layered Double Hydroxide Catalyst with High Oxygen Evolution Reaction Efficiency in Water Splitting. Issue 11 (4th May 2022) - Xie, Shijie; Liu, Changsheng; Song, Runwei; Ji, Yingxi; Xiao, Zhaohui; Huo, Chunqing; Lin, Shiwei
Abstract: Here we report a time‐saving and environmental‐friendly approach to grow sulfur doping Fe/Ni layered double hydroxide (S−FeNi LDH) catalysts on FeNi alloy sheet in five minutes at ambient temperature. It efficiently synthesizes a catalyst with multi‐layer and superlative oxygen evolution reaction (OER) activity in water splitting. The S−FeNi LDH shows overpotentials of 202 and 266 mV to deliver current densities of 10 and 100 mA/cm 2 in alkaline water respectively. The introduction of sulfur makes the catalyst more hydrophilic and changes the adsorption energy of the OER intermediates that is performed by density functional theory (DFT). This work provides an efficient strategy to improve the catalytic activity by increasing active sites and supplies a cost‐saving method to construct an effective OER catalyst for water splitting, which is extremely important for the hydrogen economy as well as environmental conservation. Abstract : Sulfur‐doped Fe/Ni layered double hydroxide on FeNi alloy sheet with high oxygen evolution reaction efficiency was developed, which can be used in the renewable energy field. Insights into the mechanism of sulfur doping are provided.